Modeling the relationship between integrated reporting quality and sustainable business development - Ciubotariu, Marius-Sorin; Socoliuc, Marian; Grosu, Veronica; Mihaila, Svetlana; Cosmulese, Cristina Gabriela (Journal of Business Economics and Management, 2021)
The aim of the paper is to provide an overview of the sensitivity in terms of the preference for using the integrated reporting quality (IRQ) based on the reporting companies’ field of activity. The study focusses on designing a sensitivity analysis relying on the most relevant financial and nonfinancial indicators as required by the stakeholders. They were adjusted by the key factors for the IRQ such as the social, natural, human and intellectual capital. The study has been designed based on the upgrade and in compliance with the connectivity principle as required by the IIRC. The data was collected from the IR examples Database between 2015–2017. The results suggest that based on sensitivity function value, those sectors of activity such as transportation and infrastructure, services and trade have a higher sensitivity preference for the IR due to the quantification of the stakeholders’ interest in terms of performance positive trend indexes. Making use of regressive techniques, the authors undertook an econometrical model for the evaluation of the IRQ that may become very useful for those companies that intend to set in place a sustainable business as it provides them the opportunity of measuring the IRQ.